Characterisation and stabilisation of recombinant humicola insolens endoglucanase produced in pichia pastoris - Abdul Fattah, S. S. (Malaysian Society of Applied Biology, 2015)
Cellulases are industrially important hydrolytic enzymes that are applicable in the bioconversion of cellulosic biomass to simple sugars. In this work, Pichia pastoris carrying an endoglucanase cDNA (CMC3) from a thermophilic fungus, Humicola insolens, was grown in a 30 L bioreactor to produce recombinant CMC3 in a fed-batch cultivation mode. After optimisation of the cultivation conditions, a total of 5.3 gL -1 proteins were obtained in a 20 L working volume after a 40 h induction with methanol. CMC3 expresses a ß-1,4-endoglucanase with a specific activity of 62.83 U mg -1 , demonstrating its specificity for hydrolysing carboxymethyl cellulose as a substrate. No detectable hydrolysis on Sigmacell ® cellulose, Avicel or beechwood xylan was observed. The recombinant CMC3 displayed moderate thermostability, being stable at up to 50°C for more than 72 h. Metal ions such as Mn² + and Co² + enhanced the CMC3 activity, while Ni + , Zn² + and Cu² + inhibited the enzyme activity. The CMC3 produced in P. pastoris was stable under long-term storage, retaining 84% and 75% of its initial activity after 4 months of storage at 4°C and 25°C, respectively. The addition of stabilisers further improved the enzyme stability by 7% and 5% at 4°C and 25°C, respectively.